Penggunaan Non Speech Oral Motor Treatment (NSOMT) Sebagai Pendekatan Intervensi Gangguan Bunyi Bicara - Hafidz Triantoro Aji Pratomo; Arif Siswanto (Jurnal Keterapian Fisik, 2020)
Background : Non Speech Oral Motor Treatment’s (NSOMT) is a collective term that require active and passive training of speech musculature (Lof & Watson, 2008). Controversy of use this method was found in several publication. Researcher notes many questions about NSOMT efication. Aim of study is to gather information about utility NSOMT among Speech Therapist’s in Central Java. Isssue of Evidence Based Practice (EBP)implementation was crucial to be answer. This study was to analyse use of NSOMT among central java clinicians who treat children with speech sound disorder. Methods: This study was conducted in March until July 2019. Total 146 speech therapist across Central Java was participated on this study. Data analysis used descriptive statistic and Spearman Rank. Results: 84,9% speech therapist in Central Java used NSOMT to treat children who have speech sound disorder. Education level had a correlation with utility NSOMT in speech sound intervention (OR: 4.61; 95%: 1.44-14.72; p: 0.010). Conclusions: The results suggested similar finding with survey was conducted before. Speech therapist needs to improve their knowledge about EBP and its implementation.